BARI-IRRI Collaborative Activity and Achievements on Homestead Farming in Bangladesh by 2024 - Ferdous, Zannatul; Bashar, H. M. K.; Talukder, Al-Amin Hossain; Islam, M. M.; Alam, Robiul; Anwar, Mazharul; Ahmed, Sharif; Bhandari, Humnath (International Rice Research Institute, 2024)
Food security in northern Bangladesh is influenced by a variety of factors, including agricultural practices, climate conditions, and socio-economic challenges. This region is primarily dependent on agriculture. Poverty, limited access to resources, and lack of diversified foods make it difficult for many households to secure adequate nutrition. To address these challenges, promoting sustainable agricultural practices, such as crop intensification diversification, homestead farming, and improved livestock management are crucial.